PDAM Info Application Innovation in the Regional Drinking Water Company (Perumda) of Makassar City - amelia chairunnisa, tarisca; Haedar Akib; Muh. Nur Yamin (Universitas Negeri Makassar, 2025)
This research aims to analyze the innovation of the PDAM Info application implemented by the Regional Drinking Water Company (Perumda) of Makassar City. As part of the e-government initiative, this application represents a significant digital transformation effort designed to enhance the efficiency and quality of services provided to the community. Employing qualitative descriptive methods, the study delves into the implementation of this application innovation. Data collection was conducted through various techniques, including direct observation, interviews with relevant stakeholders, and documentation to gather pertinent information. Data analysis utilized an interactive model, encompassing data condensation, presentation, and the drawing of conclusions or verification. The findings indicate that the implementation of the PDAM Info application innovation at the Makassar City Drinking Water Company has not achieved optimal levels across three of the five success indicators proposed by Bugge et al. Key challenges identified include governance obstacles often disrupted by technical issues such as server malfunctions and limitations in network infrastructure. Additionally, low technological literacy among the public significantly hampers widespread application usage. Other technical difficulties include limited server capacity, which prevents some application features from functioning optimally. Despite these challenges, community satisfaction surveys reveal positive feedback, particularly regarding ease of access to information and service transparency. However, the anticipated speed of service remains a critical weakness affecting the overall success of the program. Perumda continues to provide manual services to accommodate individuals who have not fully embraced digital technology. Efforts to socialize the application have been made through various communication channels, including social media, radio advertisements, and direct public meetings. Nevertheless, the effectiveness of these outreach efforts requires enhancement to reach a broader audience. Therefore, targeted strategic measures are essential to address technical challenges, improve technological literacy, and expedite service responses through the development of adequate infrastructure. In conclusion, while the PDAM Info application innovation holds promise for improving public services at Perumda Air Minum Makassar City, immediate attention to both technical and non-technical challenges is necessary to fully realize the objectives of this innovation.